Pengaruh total quality management terhadap kinerja manajerial dengan sistem pengukuran kinerja dan sistem penghargaan (reward) sebagai variabel intervening (studi empiris pada perusahaan BUMN di Kota Jambi) - Regina Nursedima Marpaung, Shinta; Hizazi, Achmad; Wiralestari, Wiralestari (Jurnal Paradigma Ekonomika, 2022)
This study aims to prove empirically (1) the effect of total quality management on managerial performance, (2) the effect of quality management (3) The effect of performance measurement systems on managerial performance. (4) The effect of total quality management on the reward system (reward) (5) The effect of the reward system on managerial performance (6) The effect of total quality management on managerial performance is mediated by the performance measurement system (7) The effect of total quality management on performance managerial mediated by the reward system. The sample used as many as 98 respondents are managers in BUMN companies in Jambi City. The results showed that (1) total quality management had a significant and significant effect on managerial performance. (2) Total quality management significantly affects the performance measurement system. (3) The performance measurement system significantly affects managerial performance in Jambi City companies. (4) Total quality management significantly affects the reward system. (5) The reward system significantly affects managerial performance in Jambi City companies. (6) Total quality management has a significant and significant effect on managerial performance mediated by the Jambi City BUMN performance measurement system. (7) The total quality of management does not have a significant and significant effect on managerial performance mediated by the reward system.